Numerical Modeling of Kerf Generation in Abrasive Waterjet Machining of Military Grade Armor Steel - Rammohan, S.; Thirumalai Kumaran, S.; Uthayakumar, M.; Velayutham, A. (Human factors and mechanical engineering for defense and safety, 2023)
The widespread usage of abrasive waterjet machining is owing to its adaptability, yet the absence of dynamic analysis throughout the kerf forming process is difficult to ensure cutting precision. The present work has proposed a linked SPH-DEA-FEM approach for predicting the cutting characteristics of abrasive water jet machining over a range of process parameters as well as for elucidating the underlying mechanism of kerf generation. Compared to the previous methods, the new simulation approach enhances the simulations of long term water jet cutting. The performance of computations is enhanced by the continuous creation of abrasive and waterjet particles, which help to keep the model short. The flow of abrasive particles that has a Gaussian distribution is described by the discrete element approach (DEA). The friction factors are concerned with the interactions of quasi particles. Smoothed Particle Hydrodynamics (SPH) approach is used to represent the water flow with large deformation. In between the particles and the target, the erosion contact is created. Finally, the simulation model validity is verified through experiments. Understanding the mechanism of abrasive waterjet cutting and optimizing the operating parameters would be beneficial.